The Immune System Can Hear Noise - Zhang, Andi; Zou, Tianyuan; Guo, Dongye; Wang, Quan; Shen, Yilin; Hu, Haixia; Ye, Bin; Xiang, Mingliang (Frontiers in Immunology, 2021)
As a stressor widely existing in daily life, noise can cause great harm to the immune system and result in many physical and mental disorders, including noise-induced deafness, sleep disorders, cardiovascular diseases, endocrine diseases and other problems. The immune system plays a major role in maintaining homeostasis by recognizing and removing harmful substances in the body. Many studies have shown that noise may play vital roles in the occurrence and development of some immune diseases. In humans, both innate immunity and specific immunity can be influenced by noise, and different exposure durations and intensities of noise may exert various effects on the immune system. Short-term or low-intensity noise can enhance immune function, while long-term or high-intensity noise suppresses it. Noise can lead to the occurrence of noise-induced hearing loss (NIHL) through the production of autoantibodies such as anti-Hsp70 and anti-Hsp60 and exert adverse effects related to other immune-related diseases such as some autoimmune diseases and non-Hodgkin lymphoma. The neuroendocrine system, mainly including the hypothalamic-pituitary-adrenal (HPA) axis and the sympathetic-adrenal-medullary (SAM) system, is involved in the mechanisms of immune-related diseases induced by noise and gut microbiota dysfunction. In addition, noise exposure during pregnancy may be harmful to the immune system of the fetus. On the other hand, some studies have shown that music can improve immune function and alleviate the adverse effects caused by noise.